2021
DOI: 10.1073/pnas.2017575118
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine fibrillar assemblies display cross-talk with Alzheimer’s disease β-amyloid polypeptide

Abstract: High levels of homocysteine are reported as a risk factor for Alzheimer’s disease (AD). Correspondingly, inborn hyperhomocysteinemia is associated with an increased predisposition to the development of dementia in later stages of life. Yet, the mechanistic link between homocysteine accumulation and the pathological neurodegenerative processes is still elusive. Furthermore, despite the clear association between protein aggregation and AD, attempts to develop therapy that specifically targets this process have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 83 publications
0
32
0
2
Order By: Relevance
“…Overall, these studies convey convincing evidence that HHcy is a major cardiovascular risk factor that potentiates dementia risk and pathogenesis, yet the causality of these effects and the molecular mechanisms linking HHcy's to increased AD risk and pathology require further investigation. Interestingly, a recent study demonstrated that Hcy has the ability to self‐assemble into amyloid‐like toxic fibrils, which can seed the aggregation of Aβ 1‐42 and increase intracellular amyloid staining in a yeast model 82 . These results open a new avenue, suggesting that metabolites, such as Hcy, can self‐assemble and cross‐seed the aggregation of pathological proteins, such as Aβ, providing a possible mechanistic explanation for the increased AD risk.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, these studies convey convincing evidence that HHcy is a major cardiovascular risk factor that potentiates dementia risk and pathogenesis, yet the causality of these effects and the molecular mechanisms linking HHcy's to increased AD risk and pathology require further investigation. Interestingly, a recent study demonstrated that Hcy has the ability to self‐assemble into amyloid‐like toxic fibrils, which can seed the aggregation of Aβ 1‐42 and increase intracellular amyloid staining in a yeast model 82 . These results open a new avenue, suggesting that metabolites, such as Hcy, can self‐assemble and cross‐seed the aggregation of pathological proteins, such as Aβ, providing a possible mechanistic explanation for the increased AD risk.…”
Section: Introductionmentioning
confidence: 98%
“…We suggest that the riboswitch-VLPs intervene earlier in the accumulation process by preventing some of the adenine to enter the yeast and then leading to fewer aggregates. To provide further support for this hypothesis, we used the ProteoStat dye that was previously shown to detect metabolite amyloid-like structures in vitro and in vivo. , The staining was followed by flow cytometry analysis, which allowed the detection of a decrease in the aggregation in the presence of the riboswitch-VLPs (Figure e,f) as well as by confocal microscopy for the identification of an intracellular localization of the aggregates (Figure g). The stained dots were not detected in the presence of the riboswitch-VLPs.…”
Section: Resultsmentioning
confidence: 98%
“…Self-assembled structures of various metabolites have also been found to induce aggregation of pathological amyloid species. Fibrillar aggregates of homocysteine have been found to display cross-talk with Aβ, 207 and amyloid-like aggregates of quinolinic acid have been observed to cross-seed αSyn aggregation. 208 Despite the recent focus and many new insights gained in the field, the molecular mechanisms underlining the interactions between different amyloid species are very limited.…”
Section: Discussionmentioning
confidence: 99%